Karakteristik Klinis Pasien Laserasi Kelopak Mata Akibat Trauma di Pusat Mata Nasional Rumah Sakit Mata Cicendo - Riza, Afdal; Kartiwa, Raden Angga (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Introduction : Trauma of eyelids due to sharp object, blunt object, road traffic accidents etc. are the major causes resulting in injuries to eyelids. A good identification and prompt treatment can improve the outcome of palpebral laceration. Purpose : To describe clinical characteristics of eyelids laceration due to trauma without involvement of lacrimal system and other orbital Methods : A retrospective descriptive cross sectional study was conducted. Data is taken from medical records of patients diagnosed as eyelid laceration from January 2016 to November 2020. Age, gender, laterality, first reference, place, onset, cause, site of trauma, depth, outcome, complication and System for Peri-Ocular Trauma (SPOT) classification was reviewed. Results : This study comprised of total 157 patients. Most of them were males 119 (75.80%) with median of age 24. The main mechanism of injury was direct trauma 88 (56.05%). The location where the injury occured was road side accidents 81 (51.59%). Superior eyelid was the most affected 96 (61.15%). Subcutaneus tissue as wound base 68 (43.31%) and affected to margin of eyelid 36 (22.92%). Hypertropic scar was the most complication found in 40 (25.47%). The most common SPOT type injury were Type IA. Conclusion : Eyelids laceration due to trauma is common in male productive age, mainly affecting superior palpebra, mostly because of road side accidents. Hypertropic scar was most complication beside traumatic ptosis, lagophthalmos and lid margin notching. The SPOT classification can simplify a recording of palpebral injuries.